A Randomized, Placebo-controlled Trial of Fidaxomicin for Prophylaxis of Clostridium difficile–associated Diarrhea in Adults Undergoing Hematopoietic Stem Cell Transplantation. (9th June 2018) - Mullane, Kathleen M; Winston, Drew J; Nooka, Ajay; Morris, Michele I; Stiff, Patrick; Dugan, Michael J; Holland, Henry; Gregg, Kevin; Adachi, Javier A; Pergam, Steven A; Alexander, Barbara D; Dubberke, Erik R; et al.
Abstract : Patients undergoing hematopoietic stem cell transplantation are at elevated risk for development of Clostridium difficile –associated diarrhea (CDAD). Fidaxomicin may have a role in the prevention of CDAD in these patients. Abstract: Background: Clostridium difficile –associated diarrhea (CDAD) is common during hematopoietic stem-cell transplantation (HSCT) and is associated with increased morbidity and mortality. We evaluated fidaxomicin for prevention of CDAD in HSCT patients. Methods: In this double-blind study, subjects undergoing HSCT with fluoroquinolone prophylaxis stratified by transplant type (autologous/allogeneic) were randomized to once-daily oral fidaxomicin (200 mg) or a matching placebo. Dosing began within 2 days of starting conditioning or fluoroquinolone prophylaxis and continued until 7 days after neutrophil engraftment or completion of fluoroquinolone prophylaxis/clinically-indicated antimicrobials for up to 40 days. The primary endpoint was CDAD incidence through 30 days after study medication. The primary endpoint analysis counted confirmed CDAD, receipt of CDAD-effective medications (for any indication), and missing CDAD assessment (for any reason, including death) as failures; this composite analysis is referred to as "prophylaxis failure" to distinguish from the pre-specified sensitivity analysis, which counted only confirmed CDAD (by toxin immunoassay or nucleic acid amplification test) as failure. Results: Of 611 subjects enrolled, 600 were treated and analyzed. Prophylaxis failure was similar in fidaxomicin and placebo recipients (28.6% vs 30.8%; difference 2.2% [-5.1, 9.5], P = .278). However, most failures were due to non-CDAD events. Confirmed CDAD was lower in fidaxomicin vs placebo recipients (4.3% vs 10.7%; difference 6.4% [2.2, 10.6], P = .0014). Drug-related adverse events occurred in 15.0% of fidaxomicin recipients and 20.0% of placebo recipients. Conclusions: While no difference was demonstrated between arms in the primary analysis, results of the sensitivity analysis demonstrated that fidaxomicin significantly reduced the incidence of CDAD in HSCT recipients. Clinical Trials Registration: NCT01691248